Empowering Communities Through Propolis Soap-Making: Behavioral Changes and Knowledge Gains in Lambadeuk Village's Sustainable Development - Fariz, Ahmad; Agussabti, Agussabti; Mujiburrahmad, Mujiburrahmad; Mukramah, Mukramah; Nugroho, Agus; Zohra, Zohra; Alsa, Muhammad Cheryl Amelin; Sarah, Siti Dwi (Journal of Innovation and Applied Technology, 2025)
Lambadeuk Village in Aceh Province is known for Trigona bees, which produce honey and propolis, a valuable by-product often discarded due to limited knowledge and skills for its utilization. This study evaluates the impact of soap-making workshop on community knowledge, behavior, and empowerment, employing Participatory Action Research (PAR). The program engaged 27 participants, primarily housewives and farmers, in theoretical and practical training on soap production using propolis. Pretest and posttest evaluations revealed significant improvements in participants' knowledge of soap-making processes and ingredient roles, with knowledge levels shifting from low to high. However, confidence for independent production remained modest, indicating the need for continued mentorship. By transforming Sustainable Development Goals (SDGs), particularly SDG 12 (Responsible Consumption and Production) and SDG 8 (Decent Work and Economic Growth). This program demonstrates the potential of targeted empowerment efforts to enhance community skills, reduce waste, and foster sustainable development through innovative resource utilization.